IMPLEMENTASI PEMBELAJARAN BAHASA ARAB BERBASIS MAHFUDZAT DI MTS AL-MUSTAQIM TANGERANG SELATAN - Rifai, Ahmad; Kamila, Devi Cahya (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2024)
This study aims to understand the application of the Mahfudzat method in learning Arabic at MTs Al-Mustaqim Bintaro. Learning Arabic through Mahfudzat is expected to improve students' vocabulary and provide a philosophy of life through teaching Arabic proverbs. The research methodology used is qualitative descriptive, where data is collected through interviews with teachers and students, as well as literature studies. The results of the study indicate that learning using Mahfudzat can help students memorize Arabic vocabulary and apply the meaning of proverbs in everyday life. Students are taught to memorize proverbs and understand their meanings, with the hope that they can apply the advice in real life. Teachers play an important role in this process, providing appropriate guidance so that students can understand the material well. In conclusion, the use of the Mahfudzat method is effective in improving students' Arabic language skills and forming noble characters